ANALYSIS OF MODERN ENCRYPTION ALGORITHMS AND THEIR IMPACT ON THE SECURITY AND EFFECTIVENESS OF INFORMATION PROTECTION - Korobeinikova, Tetiana; Kopach, Anton (Sworld-Us Conference proceedings, 2024)
Modern encryption algorithms and their impact on information security and efficiency are thoroughly examined in the article. The study covers both symmetric (DES, 3DES, AES) and asymmetric (RSA, DSA, DH) algorithms, focusing on their characteristics, adva